2017
DOI: 10.1111/scd.12225
|View full text |Cite
|
Sign up to set email alerts
|

16‐Year follow‐up of an avulsed maxillary central incisor after replantation following 10‐h storage: An unusual case

Abstract: Tooth avulsion is a type of dental injury defined as the complete displacement of a tooth out of the alveolar socket, and the lack of prompt treatment measures can result in the loss of function, poor quality of life, and psychological and social problems. However, several factors may not permit the immediate replantation of an avulsed tooth; therefore, delayed replantation has emerged as an alternative to meet the esthetic, functional, and psychological demands of patients. Here it was described that the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Apart from cultured PDL cells, PDL stem cells, bone marrow mesenchymal stem cells, adipose-derived stem cells, and other induced pluripotent stem cells have shown favorable results in reestablishing the formation of PDL cells. 24 Different literatures have presented cases in which delayed replantation had been attempted, [6][7][8][25][26][27][28][29][30][31] but most of them being <72 h of extraoral dry time, and the replanted teeth serving its function for years. 6,7,[25][26][27][28][29][30][31][32][33][34] Storage medium enhances the healing outcome of the replanted teeth.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apart from cultured PDL cells, PDL stem cells, bone marrow mesenchymal stem cells, adipose-derived stem cells, and other induced pluripotent stem cells have shown favorable results in reestablishing the formation of PDL cells. 24 Different literatures have presented cases in which delayed replantation had been attempted, [6][7][8][25][26][27][28][29][30][31] but most of them being <72 h of extraoral dry time, and the replanted teeth serving its function for years. 6,7,[25][26][27][28][29][30][31][32][33][34] Storage medium enhances the healing outcome of the replanted teeth.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 A meta-analysis conducted by Souza et al have found the incidence of internal root resorption to be 1.2%, surface root resorption to be 13.3%, inflammatory root resorption to be 23.2%, and replacement root resorption to be 51%, which shows that resorption in any form is inevitable sequelae of a replanted tooth. 6,7,25,26,29,30,34 In delayed replantation cases, root resorption is common. 3,38 In the present case, the occurrence of replacement root resorption within a month of replantation might have been due to the prolonged extraoral dry time that resulted in the destruction of PDL cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations